Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.